X-ray crystal structure and cation binding properties of a new phthalide-fused indoline derivative - Wong, Sheryn; Jalifah Latip; Nurul Izzaty Hassan; Siti Aishah Hasbullah (Penerbit Universiti Kebangsaan Malaysia, 2018)
An efficient and a green route to synthesize phthalide-fused indoline, 3-[(5-chloro-1,3,3-trimethylindolin-2-ylidene)methyl] isobenzofuran-1(3H)-one (3) has been developed by the coupling reaction of 5-chloro-2-methylene-1,3,3-trimethylindoline, 1 and 2-formylbenzoic acid, 2 under solvent-free domestic microwave irradiation. The compound was produced in 85% yield. Compound 3 was characterized by analytical and spectral methods and its structure was confirmed by chemical crystallography. Compound 3 was successfully crystallized in triclinic system with space group Pī. The molecular structure consists of fused 1 and 2 groups connected by the enamine carbon. Binding study of 3 towards different types of metal cations was done by colorimetric detection and UV-vis titrations. Compound 3 exhibited good selectivity and sensitivity for Sn2+ compared to other metal cations tested. The stoichiometric binding ratio of 3 toward Sn2+ is found to be 1:1 and the binding constant (Ka) is 1.07×104 M–1 on the basis of Job’s plot and Benesi-Hildebrand analysis.